2008
DOI: 10.1021/jp0773029
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the MnO2 Birnessite Structure upon Charge/Discharge in an Electrochemical Supercapacitor Electrode in Aqueous Na2SO4 Electrolyte

Abstract: This paper provides new insight on the charge storage mechanism in crystallized Mg-doped sodium birnessite-type manganese dioxide used as active supercapacitor electrode material that involves the intercalation/deintercalation of cations between the sheets during electrochemical reduction/oxidation, respectively. An increase of the interlayer spacing from 0.710 to 0.720 nm upon electrochemical oxidation in the presence of Na+ cations in the electrolyte is associated with the deintercalation of Na+ and the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
235
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(249 citation statements)
references
References 113 publications
12
235
2
Order By: Relevance
“…The first one implies the intercalation of protons (H + ) or alkali metal cations (C + ) (such as Li + ) in the bulk of the material upon reduction followed by deintercalation upon oxidation. 24,25 MnO 2 + H + C + + e − ↔ MnOOH (MnOOC)…”
mentioning
confidence: 99%
“…The first one implies the intercalation of protons (H + ) or alkali metal cations (C + ) (such as Li + ) in the bulk of the material upon reduction followed by deintercalation upon oxidation. 24,25 MnO 2 + H + C + + e − ↔ MnOOH (MnOOC)…”
mentioning
confidence: 99%
“…A similar result was also obtained for a layered MnO 2 . An increase of the interlayer spacing from 0.70 to 0.72 nm upon electrochemical oxidation indicated that alkaline metal cations, Na + ions, intercalated in the 2D tunnels of MnO 2 (Xu et al,2010;Athouel et al, 2008). The facts of lattice expansion and shrinkage during redox process indicated that the insertion of cations in the electrolytes predominates in the charge storage process of MnO 2 .…”
Section: +-2mentioning
confidence: 99%
“…This brings forth the search for a wide variety of materials. In general, transition metal oxides, including RuO 2 , MnO 2 , NiO, Co 3 O 4 , SnO 2 , ZnO, TiO 2 , V 2 O 5 , CuO, Fe 2 O 3 , and WO 3 (Lang et al 2011;Athoue et al 2008;Yan et al 2010;Chen et al 2012;Luo et al 2014;Liu et al 2014;Sathiya et al 2011;David et al 2014;Brezesinski et al 2009;Wang et al 2013;Liang et al 2010;Xia et al 2014;Kang et al 2013;Yu et al 2014), etc., have demonstrated high specific capacitance values with their redox reaction behaviors.…”
Section: Introductionmentioning
confidence: 99%